Visual appearance mapping for optimal vision based servoing - D. Fontanelli; P Salaris; F. A. W. Belo; A. Bicchi (Springer, 2009)
Keywords: Robotics

Variable Stiffness Actuators for Fast and Safe Motion Control - A. Bicchi; G. Tonietti; M. Bavaro; M. Piccigallo (Proceedings of the International Symposium on Robotics Research, 2003)
In this paper we propose Variable Stiffness actuation as a viable mechanical/control co-design approach for guaranteeing control performance for robot arms that are inherently safe to humans in their environment. A new actuator under development in our Lab is then proposed, which incorporate the possibility to vary transmission stiffness during motion execution, thus allowing substantial motion speed-up while maintaining low injury risk levels.
Keywords: Robotics

Visual-servoed parking with limited view angle - P. Murrieri; D. Fontanelli; A. Bicchi (Experimental Robotics VIII, 2002)
In this paper the problem of stabilizing a wheeled vehicle of unicycle type to a set point, using only visual feedback, is considered. The practically most relevant problem of keeping the tracked features in sight of the camera while maneuvering to park the vehicle is taken into account. This constraint, often neglected in the literature, combines with the nonholonomic nature of the vehicle kinematics in a challenging controller design problem. We provide an effective solution to such problem by using a combination of previous results on non-smooth control synthesis, and recently developed hybrid control techniques. Simulations and experimental results on a laboratory vehicle are reported, showing the practicality of the proposed approach.
Keywords: Embedded Control; Robotics